Contribuição do popular financial reporting para a compreensibilidade da informação contábil em universidades públicas brasileiras - Santos Filho, Manoel Francelino dos (2023)
Improving the comprehensibility of accounting and financial information in the public sector can stimulate citizen interest in checking government actions more closely, democratically bringing them closer to active participation in the public sector. In this context, the main objective of this study was to investigate the contribution of popular financial reporting - PFR in improving the understanding of accounting information by users of accounting at Brazilian public universities. The research was based on aspects of the Theory of Communication, and covered subjects that dealt with transparency in Public Administration, disclosure of accounting information in the public sector, and the PFR. The target audience consists of employees and students from the Federal University of Goias – UFG and the Federal University of South and Southeast Para – Unifesspa. Data were collected via Google's electronic questionnaire, in person, and via email, from August 27 to October 23, 2022. Methodologically, an approach was used with qualitative analysis, interpretation of information and descriptive texts from the perception of the survey respondents, and quantitative analysis, through statistical techniques that included descriptive statistics and inferential statistics. The results showed that the information reported through popular financial reporting was more comprehensible than that presented in traditional accounting reports, suggesting that the PFR has a better understanding capacity than the current reports. Also, regarding the PFR, better user satisfaction rates were observed regarding aspects related to clarity, format, form, appearance, and usefulness when compared to traditional accounting reports. In addition, it was possible to present two basic characteristics for the elaboration and presentation of the PFR: formal characteristics and content characteristics. It contributes to the discussion about the elaboration and use of the PFR, in addition to demonstrating that this type of report can help to improve comprehensibility and transparency within the scope of Brazilian public universities.